Work study of a desk computer in the clinical laboratory. Issue 5 (September 1969) - Lines, J. G.
Abstract : Calculating results from laboratory data is a time-consuming part of laboratory work, particularly in chemical pathology, and is a frequent source of mistakes. It is much less popular with technical staff than the basic laboratory work. The reasons for purchasing a desk computer, and its use to perform the calculations in a number of investigations and to convert AutoAnalyzer data into concentration units, are discussed. The introduction of a desk computer improved morale, speeded up the work, and reduced both fatigue and mistakes.